2002
DOI: 10.1246/cl.2002.1230
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Americium(III) from Lanthanide by Encapsulating Hexadentate-ligand

Abstract: Am(III) is encapsulated in an aqueous phase by a podand-type ligand, N,N,N′,N′-tetrakis(2-methylpyridyl)ethylenediamine (TPEN), and is extracted selectively over trivalent lanthanide in an organic phase using nitrobenzene. The extraction of Am(III) using TPEN shows higher selectivity and chemical stability than other conventional ones using nitrogen-donor ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…That is, in solvent extraction, a 1:1 complex forms readily for C8‐PypzH, whereas a 1:2 complex is liable to be produced for single crystals of the PypzH complex. Generally, the compositions of complexes are consistent in the crystalline and solution states in only a few cases , , . However, in most cases, the structures are different , .…”
Section: Resultsmentioning
confidence: 99%
“…That is, in solvent extraction, a 1:1 complex forms readily for C8‐PypzH, whereas a 1:2 complex is liable to be produced for single crystals of the PypzH complex. Generally, the compositions of complexes are consistent in the crystalline and solution states in only a few cases , , . However, in most cases, the structures are different , .…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that Am(III) was selectively extracted from the aqueous phase containing Ln(III) by TPEN in nitrobenzene and synergistic system with D2EHPA or decanoic acid in 1-octanol. [5][6][7] TPEN has good selectivity of Am(III) from Ln(III) and has potential to establish partitioning of minor actinides, however, there are several properties that should be improved for the application to the nuclear fuel cycle. The hydrophobicity of TPEN is one of such properties and the extractability of these trivalent metals further increases with decreasing the water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] N,N,N¢,N¢-(tetrakis-2-pyridylmethyl)ethylenediamine is recognized as a hexadentate ligand with six nitrogen donors and has been shown to chelate a variety of soft metal ions such as Hg, Cd, Au and Pd. [9][10][11][12][13] It was also shown to be effective for the chelation of f-block metals; the separation of minor actinides from high-level radioactive waste is a pressing issue. [14][15][16][17][18][19][20][21][22][23] Derivatives of TPEN have been used as extracting agents for a variety of metal ions in organic solvents.…”
Section: Introductionmentioning
confidence: 99%